Low energy availability surrogates correlate with health and performance consequences of Relative Energy Deficiency in Sport. Issue 10 (2nd June 2018) - Ackerman, Kathryn E; Holtzman, Bryan; Cooper, Katherine M; Flynn, Erin F; Bruinvels, Georgie; Tenforde, Adam S; Popp, Kristin L; Simpkin, Andrew J; Parziale, Allyson L
Abstract : Low energy availability (EA) is suspected to be the underlying cause of both the Female Athlete Triad and the more recently defined syndrome, Relative Energy Deficiency in Sport (RED-S). The International Olympic Committee (IOC) defined RED-S as a syndrome of health and performance impairments resulting from an energy deficit. While the importance of adequate EA is generally accepted, few studies have attempted to understand whether low EA is associated with the health and performance consequences posited by the IOC. Objective: The purpose of this cross-sectional study was to examine the association of low EA with RED-S health and performance consequences in a large clinical population of female athletes. Methods: One thousand female athletes (15–30 years) completed an online questionnaire and were classified as having low or adequate EA. The associations between low EA and the health and performance factors listed in the RED-S models were evaluated using chi-squared test and the odds ratios were evaluated using binomial logistic regression (p<0.05). Results: Athletes with low EA were more likely to be classified as having increased risk of menstrual dysfunction, poor bone health, metabolic issues, haematological detriments, psychological disorders, cardiovascular impairment and gastrointestinal dysfunction than those with adequate EA. Performance variables associated with low EA included decreased training response, impaired judgement, decreased coordination, decreased concentration, irritability, depression and decreased endurance performance. Conclusion: These findings demonstrate that low EA measured using self-report questionnaires is strongly associated with many health and performance consequences proposed by the RED-S models.